[The epidemiology of malaria in Elazi? and Bingöl between 2005 and 2008]. - Erensoy, Ahmet; Kuk, Salih (My University, 2010)
Malaria is a very important public health problem both for the world and Turkey. In this retrospective study, we investigated malaria using the data provided by The Health Administration of Elazi? and Bingöl between 2005 and 2008. A total of 2,380 blood smears were examined during this 4-year period and malaria was found in 9 (0.37%) in Elazi?, whereas a total of 11,548 blood smears were examined and malaria was found in 200 (0.02%) in Bingöl. All of the cases were 14 years and over and caused by Plasmodium vivax. All patients were newly arrived cases who had come to Elazi? and Bingöl from other regions for different reasons. We hope that our study contributes to the epidemiology of malaria and its prevention.
Elazi? ve Bingöl illerinde 2005-2008 yillari arasinda sitma epidemiyolojisi.
Keywords: Adolescent; Adult; Humans; Malaria, Vivax; Retrospective Studies; Turkey; Young Adult; adolescent; adult; article; human; Plasmodium vivax malaria; retrospective study; Turkey (republic)